Glycoprotein D peptide-based diagnostic approach for the detection of avian infectious laryngotracheitis antibodies. Issue 6 (2nd November 2019) - Kumar, Vishnu; Yadav, Karamchandra; Kumar, Rakesh; Chaudhary, Nitin; Kumar, Sachin
ABSTRACT: Infectious laryngotracheitis (ILT) is a highly contagious respiratory disease of chickens, pheasants, and peafowl. It is caused by the alpha herpesvirus, infectious laryngotracheitis virus (ILTV). Glycoprotein D (gD) of ILTV is immunogenic and helps in its binding to the susceptible host cell receptor. In the present study, a recombinant gD protein was expressed in a prokaryotic system to develop a single serum dilution ELISA. In addition, two immunogenic peptides, corresponding to regions 77–89 and 317–328, were identified in gD protein. The peptides were synthesized using solid-phase peptide synthesis, purified using reversed-phase HPLC, and characterized using mass spectrometry. The peptides displayed a good titre and were found to be promising antigens to coat the ELISA plate to detect the ILTV antibodies in the serum sample. The developed ELISA showed 96.9% sensitivity, 87.5% specificity, and 95.3% accuracy as compared to OIE referenced standard indirect ILTV ELISA (whole viral coated). The assay may not differentiate vaccinated from infected birds when the flocks are administered with live attenuated vaccines. However, the assay could be useful to detect the disease condition in birds vaccinated with recombinant vaccine expressing glycoproteins other than gD. The developed ILTV single serum dilution ELISA could be an alternative to the existing diagnostics for the detection of ILTV antibodies.